Design of Multi Syringe Pump for Flow System Analysis - Tri Mulyono; Asnawati Asnawati; Umarul Faruq (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2013)
The aims of this work were to research: design of the multi syringe pumps, volume consistency of ISAB and the correlation of the PWM to the flow rate of carrier. Pump speed was set by PWM. Controlling the pump speed and time were performed with a computer using Labview software. It was found that based on the time variation of time then the volume of ISAB has a consistency of the injected volume with Kv 0.25% to 2.53% and the rate of carrier based on multi syringe velocity have a good correlation with the regression value of 0.998 and the value of Kv 0.27% to 1.2%. Keywords : Multi syringe pump, MSFIA methods, PWM